A prospective study on reproductive health problems and menstrual hygiene practices among women in rural population - Biju, Vidya; Peddolla, Sushma Reddy; Inuganti, Bhavana; Gollapudi, Surendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Menstruation is defined as periodic discharge of blood from uterus occurring more (or) less at regular monthly intervals throughout the active reproductive life of a female. Hygiene-related practices of women during menstruation are considered important because it can increase vulnerability to reproductive tract infections (RTIs). Methods: A prospective, observational study was done for a period of 6 months to assess the reproductive health problems and menstrual hygiene practices among women in rural population. It was conducted by first considering RTI cases among female in-patients of obstetrics and gynaecology department at MNR hospital, Sangareddy, Telangana, on the basis of which the study was extended to certain villages of Andole Mandal, where RTIs were found to be more prevalent. The data was collected using pre designed and semi-structured questionnaire. Results: Out of 106 cases taken in the hospital, cervicitis was most prevalent 40 (37.7%). A maximum of 36 (34%) cases were from Andole Mandal, so the community-based study was done here. Among the 710 subjects considered, 206 (29%) were found to use sanitary napkins and 85 (12%) of them used disposable cloth. Majority 392 (55.2%) of the women disposed their menstrual absorbent by burning and many were presented with RTI symptoms such as lower abdominal pain, vaginal discharge. Conclusions: In the health status of women among the reproductive age group, RTIs are known to pose a serious and continuing threat, which has become a silent epidemic that devastates women’s life which is closely related with poor menstrual hygiene. Hence, there is an urgent need to provide accurate and adequate information about hygienic practices to be followed during menstruation, so as to enable them to lead a healthy reproductive life.